2023
DOI: 10.1093/jpp/rgad060
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol suppresses tumour growth and enhances chemosensitivity of 5-fluorouracil on breast carcinoma in mice: involvement of miR-21/PTEN signalling

Abstract: Objectives Breast cancer is the most diagnosed cancer in females worldwide. Phytochemicals are among the recent compelling approaches showing anticancer activity. Geraniol is a monoterpenoid showing anti-tumoral potential in cell lines. However, its exact mechanism in breast cancer has not been elucidated. In addition, the possible chemosenstizing effect of geraniol when combined with chemotherapeutic drugs in breast carcinoma has not been previously addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This reinforces geraniol as a multi-targeted anticancer agent that seems to act through several molecular pathways, a feature that increases its effectiveness for cancer control [ 179 ]. Of note, geraniol was recently shown to upregulate PTEN through the downregulation of mir-21 in an in vivo breast cancer model [ 180 ]. This suggests that the monoterpene could also modulate epigenetic processes that are key for cancer prevention.…”
Section: Mechanisms Of Pharmacological Action Of Essential Oilsmentioning
confidence: 99%
“…This reinforces geraniol as a multi-targeted anticancer agent that seems to act through several molecular pathways, a feature that increases its effectiveness for cancer control [ 179 ]. Of note, geraniol was recently shown to upregulate PTEN through the downregulation of mir-21 in an in vivo breast cancer model [ 180 ]. This suggests that the monoterpene could also modulate epigenetic processes that are key for cancer prevention.…”
Section: Mechanisms Of Pharmacological Action Of Essential Oilsmentioning
confidence: 99%
“…19 Geraniol has also displayed excellent anticancer effects in various cancer models, including breast, lung, colon, pancreatic, skin, liver, kidney, and prostate. [20][21][22][23] Carnesecchi et al utilized a mouse model with TC-118 human tumors to compare the dominant anti-tumor efficacy of geraniol with 5-fluorouracil. 22 Several studies have demonstrated that geraniol induces apoptosis and autophagy and disrupts the cell cycle pathway in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%